Effect of EDF position on the performance of hybrid dispersion-compensating Raman/EDF amplifier - Ali M.H.; Abdullah F.; Jamaludin M.Z.; Al-Mansoori M.H.; Al-Mashhadani T.F.; Abass A.K. (2023)
The effect of the location of the Erbium-doped fiber (EDF) on the performance of the hybrid dispersion compensation of Raman/EDF amplifier is discussed in this study. Two different configuration set-ups were determined according to the position of the EDF amplifier. The setup in which EDF A is positioned before is denoted by type A, while type B denotes the setup in which EDFA is positioned after. In these two amplifier configurations, the Raman gain saturation due to the Stimulated Brillouin scattering (SBS) effect is included. Type B shows a better hybrid fiber amplifier (HF A) performance in terms of overall gain, noise figure (NF), and flatness gain profile. A small signal gain of 33 and 35 dB with a flat gain bandwidth of 40 nm is achieved for types A and B, respectively. In addition, type B exhibits a high peak gain of 23 dB, with gain variation of 3 dB along 70 nm bandwidth for large input signal compared with the 17 dB peak gain of type A with gain variation of 4.4 dB along the same bandwidth. 2013 IEEE.